BODY MASS INDEX IN RELATION TO PERSONAL CHARACTERISTICS, SOCIAL ENVIRONMENT AND INDIVIDUAL`s PERCEPTIONS IN A REPRESENTATIVE POPULATION IN ROMANIA: A CASE-STUDY - Cristina Petrescu (European Scientific Journal, ESJ, 2015)
Aim of study. In this study I investigated Body Mass Index (BMI) and its relation to personal characteristics (gender, age, ethnicity), social environment (marital status, place of study), and individual weight and activity level perceptions in a statistically representative population of students in Romania. Material and method. The method was observational inquiry (case-study) and consisted of a questionnaire with 60 items from which I considered only 9 items (Q1.a–gender, Q1–age, Q2–marital status, Q3–nationality, Q49.a–weight, Q50–height, Q53–perception of own weight, Q54–perception of activity type and Q60-place of study) applied in 13 universities to 1364 students (39.3% male, 60.7% female, aged 19-30 years). The questionnaire application lasted 30 minutes and the students completed it individually and anonymously. Consent was asked for and the aim of the study was explained to participants. The Body Mass Index (BMI) was calculated using the Quetelet formula. Statistical work was performed using a SPSS 20 Program. Results. I found significant associations between: BMI– perception of the person’s own weight (χ2=449.95, Sig.=0.000; γ=0.84, Sig.=0.000), BMI-place of study (χ2=105.87, Sig.=0.000; γ=-0.15, Sig.=0.000), BMI-gender (Chi square–χ2=111.19, Sig.=0.000; gamma coefficient–γ=-0.56, Sig.=0.000) and BMI–marital status (χ2=24.28, Sig.=0.002; γ=0.27, Sig.=0.000). In conclusion a relation BMI–perception of the person’s own weight, BMI-social environment and BMI-gender is suggested.